Hyperammonaemia in critically ill septic infants. Issue 6 (1st June 2001) - McEwan, P; Simpson, D; Kirk, J M; Barr, D G D; McKenzie, K J
Abstract : Three infants with subphrenic abscess, pyonephrosis, and obstructive ureterocoele respectively had grossly increased concentrations of plasma ammonia. This was considered to be a result of infections with urea splitting organisms. All died in spite of intensive care support, including specific measures to reduce plasma ammonia.